Diamondback Moth, Plutella xylostella (Linnaeus) (Insecta: Lepidoptera: Plutellidae) - John L. Capinera (EDIS)
This document is EENY-119, one of a series of Featured Creatures from the Entomology and Nematology Department, Florida Cooperative Extension Service, Institute of Food and Agricultural Sciences, University of Florida. Published: January 2000. Revised: May 2000.